A randomised, double blind, placebo controlled study of celecoxib, a selective cyclooxygenase 2 inhibitor, on duodenal polyposis in familial adenomatous polyposis. Issue 6 (1st June 2002) - Phillips, R K S; Wallace, M H; Lynch, P M; Hawk, E; Gordon, G B; Saunders, B P; Wakabayashi, N; Shen, Y; Zimmerman, S; Godio, L; Rodrigues-Bigas, M; Su, L-K; et al.
Abstract : Background: Non-selective cyclooxygenase (COX) inhibitors (non-steroidal anti-inflammatory drugs) inhibit large bowel carcinogenesis in patients with familial adenomatous polyposis (FAP). Their role in the duodenum of these patients is less certain. The disease modifying activity of specific COX-2 inhibitors has not been explored in humans. Patients and methods: This was a randomised, double blind, placebo controlled study of celecoxib (100 mg twice daily (n=34) or 400 mg twice daily (n=32)) versus placebo (n=17), given orally twice daily for six months to patients with FAP. Efficacy was assessed qualitatively by blinded review of shuffled endoscopy videotapes comparing the extent of duodenal polyposis at entry and at six months and quantitatively by measurement of the percentage change in duodenal area covered by discrete and plaque-like adenomas from photographs of high and low density polyposis. Results: Shuffled and blinded video review showed a statistically significant effect of 400 mg twice daily celecoxib compared with placebo treatment (p=0.033) with all five independent observers scoring a beneficial effect. Overall, patients taking celecoxib 400 mg twice daily showed a 14.5% reduction in involved areas compared with a 1.4% for placebo (p=0.436). However, patients with clinically significant disease at baseline (greater than 5% covered by polyps) showed a 31% reduction in involved areas with celecoxib 400 mg twice daily compared with 8% on placebo (p=0.049). Conclusions: A panel of five endoscopists found a significant reduction in duodenal polyposis after six months of treatment with celecoxib 400 mg twice daily. COX-2 inhibition may help this otherwise untreatable condition.